2006
DOI: 10.1002/bjs.5423
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided foam sclerotherapy for the treatment of varicose veins

Abstract: UGFS achieved early complete occlusion safely in over 90 per cent of legs with varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 20 publications
4
48
0
1
Order By: Relevance
“…Our outcome parameter are similar to those quoted in the literature [2][3][4][5][6] with negligible complication rates and high degree of initial success rates with 15 legs (89%) achieving complete closure with a single injection and all patients achieving closure with two injections.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our outcome parameter are similar to those quoted in the literature [2][3][4][5][6] with negligible complication rates and high degree of initial success rates with 15 legs (89%) achieving complete closure with a single injection and all patients achieving closure with two injections.…”
Section: Discussionsupporting
confidence: 86%
“…Ultrasound guided foam sclerotherapy is one such option it was introduced in 2001 by Tessari et al [1]. Foam sclerotherapy has been used with very low complication rates and with success rates up to 90% [2,3]. In this article we present our two needle technique of ultrasound guided foam sclerotherapy along with our short term results.…”
Section: Introductionmentioning
confidence: 94%
“…For the remaining four legs (5%) a further single session of foam injections directly into the visible varicosities successfully treated the residual VV in the remaining four legs. These results were comparable with other studies as Darke and colleagues study [11] who treated 18 legs with UGFS; Ten legs (55.55%) had complete occlusion after one treatment; a further five (27.77%) had complete occlusion after two treatments. The three remaining legs had partial occlusion (either GSV still open but varicosities all closed or less than complete GSV occlusion but patient satisfied) after one, two or three treatments.…”
Section: Citationsupporting
confidence: 90%
“…These results are comparable to those achieved with surgical or other interventional endovascular procedures. 7,[10][11][12][13][14][15][16][17][18][19] Our study consisted of a representative number of patients with uncomplicated VVs (59%) and severe venous insufficiency (41%) referred to a vascular outpatient clinic. We have demonstrated that the rate of complete and partial obliteration does not differ between these patients.…”
Section: Discussionmentioning
confidence: 99%
“…12 Other studies report similar results. [13][14][15][16][17] Two recent systematic reviews and meta-analyses including randomized controlled trials, prospective cohort studies and retrospective case series have evaluated the efficacy of EFS compared with other endovenous ablation and surgical stripping. 18,19 The first review evaluated 10 studies using EFS, most involving less than 100 patients all performed outside the US, and found that it was as effective as surgical stripping for the treatment of VVs, but less effective than EVLT.…”
Section: Adverse Eventsmentioning
confidence: 99%